Pengembangan Model Pembelajaran Berbasis Project Untuk Meningkatkan Kecakapan Hidup (Life Skill) Pada Mata Pelajaran IPS di SMP Kota Tegal - Khamidah, Anis Khamidah; Suriswo, Suriswo; Apriani, Dewi (Cakrawala: Jurnal Pendidikan, 2025)
Project-based learning model (PBL) as one of the innovative learning models based on students (student center) can be used and selected by teachers as one of the alternative learning methods that will provide a new "color" in learning from the generally conventional ones. The purpose of this study is to produce a project-based learning model that is feasible to improve life skills in social studies lessons in junior high schools and to describe and analyze the effectiveness of the project-based learning model that is effectively adapted to improve life skills in social studies lessons in junior high schools. The type of research used in this study is Research and Development (R&D). This study uses Borg & Gall's research and development procedures which are the basis for developing a project-based learning model to improve life skills in social studies subjects in grade VIII junior high schools. The data collection technique for this study uses Observation, Interviews, Test Questionnaires. Data analysis of the effectiveness of the project-based learning model to improve life skills in social studies lessons in junior high schools uses the Wilcoxon test. The conclusion of this study shows that 1) The current social studies learning in junior high schools is that teachers have not fully developed teaching materials that are oriented towards life skills. 2) The project-based learning model has proven to be effective in improving life skills. The results of the assessment by teachers get a Good category. This result is also supported by an increase in life skills. The calculation of the increase in life skills in three aspects, namely attitude, knowledge and skills, gets a significance value below 0.05 so that it can be interpreted that there is a significant difference in life skills before the pretest and after the posttest. Keyword: project based learning, life skills, social studies learning